2015
DOI: 10.4028/www.scientific.net/amm.773-774.1365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Biomedia Performance for River Purification: Preliminary Stage

Abstract: There is national concern about rivers pollution degree. The Malaysian Department of Irrigation and Drainage (DID) is running a project for river biological purification using biomedia to reduce the river pollution degree. This study aims to use different types of biomedia carrier for effective management of the river purification plant project. Water samples were collected and tested for various essential parameters. A biomedia laboratory setup was fabricated for the research with seven different types of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Gasim et al (2015,2016) [41,42] evaluate the efficiency of plastic materials for water treatment. The similar method was also applied to explore the differences of microbial communities of biofilms on plastic substrates and natural substrates [28][29][30].…”
Section: Biofilm Community Diversity On Microplasticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gasim et al (2015,2016) [41,42] evaluate the efficiency of plastic materials for water treatment. The similar method was also applied to explore the differences of microbial communities of biofilms on plastic substrates and natural substrates [28][29][30].…”
Section: Biofilm Community Diversity On Microplasticsmentioning
confidence: 99%
“…The results indicated that PMMA and PET can act as new habitats for biofilm colonization, which may further disturb biofilm communities and change biogeochemical processes in aquatic ecosystems, for example, carbon, nitrogen and phosphorus cycles [41,42]. Therefore, the massive plastic waste produced in the city should be managed efficiently and treated in a proper way to minimize the impact.…”
Section: Practical Implications Of This Studymentioning
confidence: 99%